The play's the thing. (Economist, 2011)
The article considers alternative uses of video games in which the virtual reality technology used in such games is applied to real world purposes. The video game company Codemasters, which creates automobile racing games, is among the examples cited, as its computer simulation software was used by Grand Prix racing drivers as a form of training before racing on a new racetrack. So-called "gamification" in which principles of game playing are applied to business operations is examined.